Symmetries, Associated First Integrals, and Double Reduction of Difference Equations - L. Ndlovu; M. Folly-Gbetoula; A. H. Kara; A. Love (Abstract and Applied Analysis)
We determine the symmetry generators of some ordinary difference equations and proceeded to find the first integral and reduce the order of the difference equations. We show that, in some cases, the symmetry generator and first integral are associated via the “invariance condition.” That is, the first integral may be invariant under the symmetry of the original difference equation. When this condition is satisfied, we may proceed to double reduction of the difference equation.